Transcriptome analysis alk-SMase knockout mice reveals the effect of alkaline sphingomyelinase on liver - Jiang Zhu; Lingqi Wang; Xin Li; Dexu Lan; Lei Song; Yichen Li; Yuqi Cheng; Ping Zhang (Biochemistry and Biophysics Reports, 2022)
Alkaline sphingomyelinase (alk-SMase) is phospholipase that creates ceramides and inactivates platelet activating factors during metabolism, and is linked to digestion and cancer prevention. There have been few studies that completely investigate the linked function and identify the genes related to alk-SMase. In this work, RNA sequencing was performed to investigate the function of alk-SMase. Using RNA-seq data, we discovered 95 differentially expressed genes in the liver of wild type (WT) mice and alk-SMase (gene NPP7) knockout (KO) mice. Differentially expressed genes were functionally associated with the inflammatory response, steroid metabolic process and TNF signaling pathway related terms, regulation of carbohydrate biosynthetic process, and Cytochrome P450-arranged by substrate type using Metascape, according to the results of gene ontology functional enrichment analysis. In addition, an integrated PPI and KEGG network was used to investigate the relationship of differentially expressed genes, It was discovered that one module, which contained 21 nodes and 23 interactions, was significantly related to Cytochrome P450 family, which as mediator of phospholipase. To corroborate the RNAseq results, we identified 12 important genes with high expression levels and significant differences in RNAseq for quantitative real-time polymerase chain reaction (qPCR) verification; 7 genes showed difference significantly (P < 0.05). Our research is the first to conduct a comprehensive genome-wide analysis of the alk-SMase knockout model. Alk-SMase is involved in sphingomyelin hydrolysis. In liver tissues lacking alk-SMase expression, the expression levels of seven genes, including Cyp4a14 and Cyp4a10, were altered.